Democracy in Practice
XIII, 275 p.
Keywords: This collection makes a compelling case for the importance of studying ceremony and ritual in deepening our understanding of modern democratic parliaments. It reveals through rich case studies that modes of behaviour, the negotiation of political and physical spaces and the creation of specific institutional cultures, underpin democracy in practice.